FEATURES OF IMAGE DESIGN OF THE POLITICAL PARTIES: PHENOMENON AND STRUCTURAL COMPONENTS - Сливка, Н. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article analyzes the phenomenon of political image as a major factor in electoral choice by characterization of structural components of the party’s image and the main principles of its construction. Particular attention emphasizes the mainstreaming of image formation of political parties in Ukraine.